Sosialisasi dan Pendampingan Dalam Pembuatan Tipografi Kepada Masyarakat Desa Penanggungan - Amanda Shafarissa Kusnanto (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
This research describes community service activities in the form of educational outreach about making typefaces at SMA Negeri 1 Trawas. Previously, teachers and students had limited understanding of typography and also how to use design applications such as AI, PS, and Canva. This socialization activity was carried out on 22 and 24 August 2023, involving all teaching teachers, school principals and also student affairs. The socialization began with a speech from the Principal, which was then continued with a presentation of material on Basic Typography and Applied Typography by one of the Bina Desa students. Participants are given guidance when practicing regarding the use of design applications, and also how to upload fonts on the Calligraphr website. Although the skill levels of the teachers and students varied greatly, the enthusiasm of the teachers and students was very high, and this activity was also considered a success, in delivering the material, as well as in providing practical training in letter making. The success of this activity was largely due to the way the material and practices were delivered by the resource persons, as well as the use of language that was easy to understand. In conclusion, although the skill level of each individual is different, this activity succeeded in growing the interest and enthusiasm of the participants.